2023
DOI: 10.5194/egusphere-egu23-15292
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Research on the effect of urban territorial expansion on thermal environment using the inverse S-function curve- Taking Beijing-Tianjin-Hebei China Capital Economic Circle as an Example

Abstract: <p>The inverse S function can not only fit the spatial attenuation of construction land density, but also fit the spatial attenuation characteristics of various urban characteristics. Therefore, we assume that the inverse S-function curve is also applicable to the spatial variation law of urban LST. We hope to conduct an inverse S function model fitting analysis of the surface temperature of the three major cities in Beijing, Tianjin, Hebei, China's capital economic circle in 2001 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Typically, a reference illuminance of 500 lux is recommended for office task areas. However, research has shown that the demand for illuminance in task areas often exceeds these standards, especially during high-intensity mental work conducted over short periods [10][11][12]. The European indoor lighting standard as UNE-EN 12464-1-2012 [13] recommends that the reference illuminance of office task areas is 500 lux.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, a reference illuminance of 500 lux is recommended for office task areas. However, research has shown that the demand for illuminance in task areas often exceeds these standards, especially during high-intensity mental work conducted over short periods [10][11][12]. The European indoor lighting standard as UNE-EN 12464-1-2012 [13] recommends that the reference illuminance of office task areas is 500 lux.…”
Section: Introductionmentioning
confidence: 99%